Pengaruh Latihan Zigzag terhadap Dribbling pada Sepak Bola Menggunakan Kaki Bagian dalam pada Siswa Kelas IX di SMP IP Baitussalam Kuningan - Muhamad Rifky Alviansyah; Didi Muhtarom (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to investigate the effect of zigzag training on dribbling skills using the inside of the foot among ninth-grade students at SMP IP Baitussalam Kuningan. The research problem arises from the importance of dribbling as one of the fundamental techniques in football that students are required to master. The research employed an experimental method with a one-group pretest–posttest design. The sample consisted of 15 students selected through purposive sampling based on specific criteria, including active participation in physical education classes and involvement in extracurricular football activities. The research instrument was a dribbling skill test conducted in two stages: the pre-test, administered before the treatment, and the post-test, carried out after students completed ten training sessions of zigzag exercises. Data analysis using the paired sample t-test revealed a significant difference between pre-test and post-test results. The obtained Sig. (2-tailed) value was 0.000 (< 0.05), indicating that the research hypothesis was accepted. These results demonstrate that zigzag training has a significant positive effect on improving dribbling skills using the inside of the foot. Moreover, the training also enhanced students’ agility, speed, and ball control. The findings highlight that structured and varied training methods can provide more optimal outcomes in the learning process of basic football skills. Therefore, zigzag training can serve as an effective and applicable alternative method in physical education to improve students’ technical abilities, particularly in mastering fundamental football techniques such as dribbling.